Միջնադարյան վարդապետարանները և ազգային ինքնությունը - Բարխուդարյան, Վլադիմիր («Նաիրի» հրատ.)
A number of clerical colleges were established in numerous cities and monasteries of Armenia and Cilicia. More prominent among them was the college of Gladzor, which has been called a university and was considered as ―second Athens‖.
Keywords: Քրիստոնեություն; Վարդապետություն